Political parties and the quality of democracy. The peruvian case - Miro Quesada Rada, Francisco (2018)
This article deals with the ways in which the special law establishes the democratic functioning of political organizations in terms of the transparency that they must exhibit as to the origin of the economic resources that support it, and the procedure for access to the free use of space -those offered by state-owned social media in proportion to the last general election result; and specifies the rules so that political parties can testify to political pluralism and that the formation of the popular will and the internal electoral processes as well as the fundamental institutions in their purpose of energizing the political articipation of the citizens as the basis of the democratic system.